ANALISIS PENTINGNYA KECERDASAN EMOSIONAL DALAM PENINGKATAN KINERJA PEGAWAI PADA BIDANG PAUDNI DINAS PENDIDIKAN KOTA SUNGAI PENUH: ELIYUSNADI, S.Kom., M.Si - Eliyusnadi (LPPM STIA Nusantara Sakti, 2019)
Analisys of Intelegence Emotional of employees at Office Dinas Pendidikan Sungai Penuh City. This study aims to determine the Intelegence Emotional of employee work at early chilhood edication field of ation office of full river city. The Research methode research is qualitatif approach by doing interview method. The number of informants in this study is as many as seven people. Indicators for motivation variables based on Gibson opinions consisting of emphati, expectations and incentives. Based on the result showed that the employee’s Intelegence Emotional of is Good. Where this is contrary to the phenomenon that occuret in the research.